Comparison of Continuous and Periodic Exercise on Serum Nitric Oxide Level and Vascular Endothelial Growth Factor in Old Rats - Abdolhamid Zokaei; Mehran Ghahramani; Golbano Bolouri; Mahdieh Nassiri Avanaki (Medical Laboratory Journal, 2023)
Background and objectives: Considering the importance of aging and the associated physiological changes, as well as the effects of exercise on angiogenesis and cardiac index, this study aimed to compare continuous and periodic exercise in form of high-intensity interval training (HIIT) on serum levels of nitric oxide (NO) and vascular endothelial growth factor (VEGF) in old rats. Methods: In this study, 30 old male rats were randomly divided into three groups: continuous training (n=10), HIIT (n=10), and control group (n=10). Interventions were performed for 8 weeks. To evaluate the research variables, 72 hours before the first training session and after the last training session, 3 ml of blood were taken from the tails of the rats. One-way analysis of variance was used to analyze the findings and Levene's test was used for assessing the homogeneity of variance. All statistical tests were performed using SPSS 17 software at a significance level of 0.05. Results: Both training exercises significantly increased NO and VEGF levels compared to the control group (p<0.05). Conclusion: The results of this study showed that 8 weeks of continuous and interval training cause a significant increase in the level of angiogenic factors in old rats. Therefore, these exercises and especially alternative exercises can be used as a suitable way to increase angiogenesis in the elderly.